Temporal and environmental influences on the vocal behaviour of a nocturnal bird. (27th June 2014) - Digby, Andrew; Towsey, Michael; Bell, Ben D.; Teal, Paul D.
<x xml:space="preserve">Abstract</x> Temporal and environmental variation in vocal activity can provide information on avian behaviour and call function not available to short‐term experimental studies. Inter‐sexual differences in this variation can provide insight into selection effects. Yet factors influencing vocal behaviour have not been assessed in many birds, even those monitored by acoustic methods. This applies to the New Zealand kiwi (Apterygidae), for which call censuses are used extensively in conservation monitoring, yet which have poorly understood acoustic ecology. We investigated little spotted kiwi Apteryx owenii vocal behaviour over 3 yr, measuring influences on vocal activity in both sexes from time of night, season, weather conditions and lunar cycle. We tested hypotheses that call rate variation reflects call function, foraging efficiency, historic predation risk and variability in sound transmission, and that there are inter‐sexual differences in call function. Significant seasonal variation showed that vocalisations were important in kiwi reproduction, and inter‐sexual synchronisation of call rates indicated that contact, pair‐bonding or resource defence were key functions. All weather variables significantly affected call rates, with elevated calling during increased humidity and ground moisture indicating a relation between vocal activity and foraging conditions. A significant decrease in calling activity on cloudy nights, combined with no moonlight effect, suggests an impact of light pollution in this species. These influences on vocal activity provide insight into kiwi call function, have direct consequences for conservation monitoring of kiwi, and have wider implications in understanding vocal behaviour in a range of nocturnal birds.